2015
DOI: 10.1209/0295-5075/111/26001
|View full text |Cite
|
Sign up to set email alerts
|

Opening and retraction of particulate soap films

Abstract: We study for the first time the bursting dynamics of thin liquid films laden with hydrophobic micronic particles either with free or constrained edges. We highlight that the particles can arrange in bilayer or monolayer configurations and explore a range of particles coverage from zero to random close packing. When the particles bridge the two interfaces (monolayer configuration) of free edge films, the hole opens intermittently. For the other cases, we observe constant retraction velocities, modeled by balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Finally, the role of film inhomogeneities should also be investigated. We indeed observed that bare zones of the film (without cement particles), visible for instance in figure 4b, are more prone to bursting, as reported in the literature in other configurations for model particulate systems 24,25 .…”
Section: Possible Criteria For Film Generationsupporting
confidence: 88%
See 1 more Smart Citation
“…Finally, the role of film inhomogeneities should also be investigated. We indeed observed that bare zones of the film (without cement particles), visible for instance in figure 4b, are more prone to bursting, as reported in the literature in other configurations for model particulate systems 24,25 .…”
Section: Possible Criteria For Film Generationsupporting
confidence: 88%
“…Finally, how dynamical processes and the presence of particles modify film stability remains an open question. Whereas the formation of soap films is known to be governed by surface mechanical properties 21 , which are dramatically modified by the presence of particles 22 , less is known about film stability, which depends on the mechanical deformation or stress 23 and on the presence of particles that can either inhibit 24 or trigger rupture 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Horozov et al [8] showed that the bridging configuration is obtained mostly when repulsive forces exist between the particles. More recently, Timounay et al [10] created free-standing particle films, by dipping and removing a frame through a particle raft (Figure 1-b), for which the particles can arrange in bilayer or monolayer configurations depending on particle sizes and geometry of the frame. They showed that the particle configuration influences the bursting dynamics of armored liquid films.…”
Section: Introductionmentioning
confidence: 99%
“…The contact angle between the grain and the water is measured by trapping a single bead at the surface of a pending drop of liquid (Timounay, Lorenceau & Rouyer 2015). For each experiment, the granular packing is prepared by following a protocol detailed in Appendix A.…”
Section: Experimental Methodsmentioning
confidence: 99%